Дом, где исполняются мечты: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Экcмо, 2016)
Экземпляры: ф.15 (20180406) / Инвентарный номер: 49834 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44